Accuracy and reliability of a three-dimensional superimposition method for maxillary jaws and dentition - Qifei Yang; Minchun Cai; Shushu Hao; Huihan Chu; Yuting Wang; Ming Hu; Hui Yang; Zhendong Wang (BMC Oral Health)
Abstract Objective This study aims to develop a method for three-dimensional (3D) superimposition of the maxillary jaws and dentition using Cone Beam Computed Tomography (CBCT) and intraoral scan data, and to evaluate its accuracy and reliability. Materials and methods This study included 32 adult patients with Angle Class II malocclusion who underwent clear aligner therapy (CAT). The patients were categorized into two groups: Group 1 (TMEM: Third Molar Extraction Management group), including 16 individuals who had undergone maxillary third molar extraction prior to treatment. Group 2 (RMEM: Retained Maxillary Third Molar group), consisting of 16 patients who retained their maxillary third molars throughout the treatment period. CBCT scans and intraoral scan data were obtained at pre-treatment and post-treatment stages. Voxel-based superimposition and surface-based alignment techniques were applied to register the CBCT images before and after treatment. Subsequently, the digitized maxillary dentition model from intraoral scans was integrated with the CBCT dataset. Image alignment was performed, and its accuracy was verified. The precision and reliability of both alignment methods were systematically evaluated. Results The measurement results revealed that the average alignment accuracy of the CBCT images before and after treatment was 0.52 ± 0.03 mm (0.52 ± 0.03 mm in the TMEM group and 0.53 ± 0.03 mm in the RMEM group, the difference between the two groups was not significant, p = 0.782, p > 0.05), while the average alignment accuracy of the intraoral scan model integrated onto the CBCT images was 0.20 ± 0.02 mm (0.20 ± 0.01 mm in the TMEM group and 0.20 ± 0.01 mm in the RMEM group, the difference between the two groups was not significant, p = 0.551, p > 0.05). All registration methods demonstrated excellent inter-examiner reproducibility within each group (ICC > 0.9). Conclusion This study identified a reproducible and reliable method for 3D superimpose of the maxillary jaw and dentition before and after orthodontic treatment. This method can be used to assess changes in the position of the maxillary dentition and jaw morphology following orthodontic treatment.